ANALYSIS DEFINITIONS OF BASIC RESEARCH INFORMATION CULTURE OF FUTURE navigators - Sherman, М.І.; Bezbah, О.М. (Journal of Information Technologies in Education (ITE), 2016)
Based on analysis of data sources, professionally-oriented products with cultural and activity approaches clarified the definition of basic research - "information activities","information behavior", "information need", "world news". It was found that the information needs of the individual are in fact in the information needs of human activities in order to eliminate the mismatch between the current and the normal state of the information sphere of the subject in the information society. It has been established that the information requirements have pronounced social and informational nature, are divided into sensory, social and professional structure of information requirements established communication, cognitive, mnemonic, aesthetic,regulatory, professional components, and they are the driving forces of human information. In theory reasonable and entered in a scientific appeal definition "informative activity of future navigators", under that we understand totality of the actions, sent to satisfaction of their informative requirements in social, cognitive and practical spheres of professional and personality activity the aim of that is providing of steady professional development and personality adaptation of future navigators in the conditions of global informative society. It is certain that her structure is formed by informatively-legal, research and information, informatively-communicative, informatively-administrative, informatively-documentary, informatively-operator constituents.The analysis of maintenance of terms is executed "informative literacy", "informative form","informative competence", "informative culture" and lined up their hierarchy as sequence of the stages of forming of informative culture of future navigators.